Which morphological scoring system is relevant in human embryo development? - Montag, Markus; Bender-Liebenthron, Jana; Köster, Maria (Placenta, 2011)
Objectives - In the past several scoring systems were proposed for early human development aiming to assist in the identification of the best embryos. Scoring criteria are usually assessed at static developmental time points by microscopy. For almost every scoring system controversial results on its benefit can be found in the literature. With the introduction of time-lapse imaging static assessment of developmental parameters needs to be revised. The objective of this study was to critical review the strategy of static assessment by using an embryo monitoring system to study time-dependent variations of scoring criteria. - Study design - Human oocytes were subjected to intracytoplasmic sperm injection and subsequently incubated in an embryo monitoring device. Images from individual oocytes were captured at given time intervals allowing a time-lapse analysis of early embryo development. - Main outcome measures - Scoring of pronuclear morphology, early cleavage and embryo morphology up to day 3 of development was performed at standard time points and compared to the morphological fate present in time intervals prior and after standard assessment. - Results - Pronuclear morphology showed a high variability within very short time intervals. First cleavage can be observed at very early time points questioning the criterion “early cleavage”. Embryo morphology can change within short time intervals and thus may be misleading if assessment is done at a static time point. - Conclusions - Scoring of early embryo development has limitations if based on static observation only. Time-lapse imaging will lead to revised scoring systems emphasizing the need for a new look on embryological parameters.
Gesehen am 07.09.2022